Cardiovascular and Systemic Risk in Nonalcoholic Fatty Liver Disease Atherosclerosis As a Major Player in the Natural Course of NAFLD - Lonardo, Amedeo (2013)
Non-alcoholic fatty liver disease (NAFLD) encompasses pure steatosis through nonalcoholic steatohepatitis (NASH) and is the most common cause of chronic liver disease in Western countries. NASH is a progressive liver disease that increases the risk of cirrhosis and end-stage liver disease. Interestingly, the global health risk of NAFLD is not confined to the liver. Compared with those without NAFLD, patients with NAFLD exhibit not only increased liver-related complications and liver-related mortality but also increased risk of developing type 2 diabetes, cardiovascular disease (CVD) and chronic kidney disease, increased risk of post-operative complications after major liver surgery, and increased risk of developing certain malignancies, including primary liver cancer and colorectal cancer. In this review, we discuss the current evidence linking NAFLD with the risk of CVD in the setting of the more complex scenario of other hepatic and extra-hepatic complications that may occur during the natural course of NAFLD. Moreover, we provide a brief description of the putative biological mechanisms underlying such complications, particular emphasis being given to CVD. We conclude that NAFLD is a complex health problem with implications far beyond the liver. Hence, it may cause a significant global health burden and the assistance of patients with NAFLD impacts on the work of physicians from many different medical specialties.